Radial shock wave and a tailored exercise program on axillary web syndrome after breast cancer surgery with axillary dissection: a controlled clinical trial - Elgohary, Hany; Elkholi, Mohamed; Abdelaziz, Rehan (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. The study evaluated the eﬀectiveness of combining radial shock wave therapy and a tailored exercise program for treating axillary web syndrome after breast cancer surgery.Methods. Ninety-three eligible patients were randomly divided into three groups who received radial shock waves and a tailored exercise program (group A), shock wave therapy (group B), or a tailored exercise program (group C). All three groups underwent treatment over 4 weeks and were assessed for shoulder ﬂexion and abduction, pain, thickness, echogenicity, cord disorgani-sation, and abbreviated disabilities of the arm, shoulder and hand (Quick DASH) assessment at the beginning and end of the interventions. The statistical analysis included descriptive statistics, tests for homogeneity, chi-squared tests, interquartile range, Kruskal–Wallis tests, and one-way analysis of variance (ANOVA) with post hoc Tukey.Results. After the 4-week interventions, the mean diﬀerences in outcome measures indicated signiﬁcant variations among the groups. Speciﬁcally, group A exhibited mean diﬀerences of –7.9 and –6.87 for shoulder ﬂexion compared to groups B and C, respectively. For shoulder abduction, group A had mean diﬀerences of –20.17 and –10.28 compared to groups B and C, while group B exhibited a mean diﬀerence of 9.89 compared to group C. Additionally, distinct mean diﬀerences were observed for visual analogue scale (VAS), cord thickness, and Quick DASH across the groups.Conclusions. The results suggest that combining radial shock wave therapy with a tailored exercise program provides greater beneﬁts compared to the exercise program or radial shock wave therapy alone for patients who have undergone breast cancer surgery with axillary dissection.
Keywords: lymphatic cording; breast neoplasms; dissection; exercise therapy; radial shock wave